Manufacturing Industry Production Chain In Jebres District, Surakarta (Case Study: Nira Faro Industry) - Risnandar, Hian; Ramadhan, Ibnu Sina; Zinan, Muhamad Roudhul; Anggani, Nirma Lila (Urecol Journal. Part E: Engineering, 2025)
Small and medium industries have an important role in strengthening the local economy. This study aims to determine the production chain system in the Nira Faro Industry in Jebres District, Surakarta City. The method used is descriptive qualitative through observation, interview, and documentation. The results showed that Nira Faro industry is an independent industry with a made to order production system. Nira Faro industry uses raw materials from outside the city with limited labor and marketing directly and online. Production activities are carried out simply with human labor. In conclusion, although it is run simply, the Nira Faro industry is able to survive and develop even though it still needs improvement in strengthening the business network